2021
DOI: 10.21203/rs.3.rs-63480/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors contributing to men’s grief following pregnancy loss and neonatal death: further development of an emerging model in an Australian sample

Abstract: Background: Historically, men’s experiences of grief following pregnancy loss and neonatal death have been under-explored in comparison to women. However, investigating men’s perspectives is important, given potential gendered differences concerning grief styles, help-seeking and service access. Few studies have comprehensively examined the various individual, interpersonal, community and system/policy-level factors which may contribute to the intensity of grief in bereaved parents, particularly for men. Metho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, Meredith et al also noted the important effects on the wider family unit which were not assessed here [7]. Given that (male) partners experience 12 different challenges after a baby dies [16,17], further research is needed to investigate whether a specialist antenatal service for pregnancy after loss improves partner's and other family member's experience of subsequent pregnancies as well as the having a positive impact on the parental relationship . Likewise, more work is needed to understand the emotional and psychological experiences of both parents following birth of a live baby.…”
Section: Contextualising the Findingsmentioning
confidence: 99%
“…However, Meredith et al also noted the important effects on the wider family unit which were not assessed here [7]. Given that (male) partners experience 12 different challenges after a baby dies [16,17], further research is needed to investigate whether a specialist antenatal service for pregnancy after loss improves partner's and other family member's experience of subsequent pregnancies as well as the having a positive impact on the parental relationship . Likewise, more work is needed to understand the emotional and psychological experiences of both parents following birth of a live baby.…”
Section: Contextualising the Findingsmentioning
confidence: 99%
“…Similar to previous studies, in this study, the prevalence of PTSD in mothers who experienced TOPFA was 21.3%, and 62.7% of mothers were at clinical risk of PTSD (Cao et al, 2016). The effects of TOPFA on mothers have been extensively studied, but the effects on fathers are understudied (Christiansen, 2017; Obst et al, 2021). Studies have shown that fathers have similar levels of PTSD to those of mothers, with a prevalence of 15.6% being reported (Turton et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, couples experiencing PTSD are less able to provide emotional support to each other, which is not conducive to alleviating psychological stress. Therefore, to promote the psychological adjustment of couples, healthcare providers should provide psychological guidance and interventions for both mothers and fathers, and reduce negative psychological interactions between them (Nguyen et al, 2019; Obst et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations